Complement component C5a mediates hemorrhage-induced intestinal damage - Fleming, Sherry D.; Phillips, Lauren M.; Lambris, John D.; Tsokos, George C. (My University, 2013)
Background: Complement has been implicated in the pathogenesis of intestinal damage and inflammation in multiple animal models. Although the exact mechanism is unknown, inhibition of complement prevents hemodynamic alterations in hemorrhage. Materials/Methods: C57Bl/6, complement 5 deficient (C5-/-) and sufficient (C5+/+) mice were subjected to 25% blood loss. In some cases, C57Bl/6 mice were treated with C5a receptor antagonist (C5aRa) post-hemorrhage. Intestinal injury, leukotriene B4, and myeloperoxidase production were assessed for each treatment group of mice. Results: Mice subjected to significant blood loss without major trauma develop intestinal inflammation and tissue damage within two hours. We report here that complement 5 (C5) deficient mice are protected from intestinal tissue damage when subjected to hemorrhage (Injury score = 0.36 compared to wildtype hemorrhaged animal injury score = 2.89; p<0.05). We present evidence that C5a represents the effector molecule because C57Bl/6 mice treated with a C5a receptor antagonist displayed limited intestinal injury (Injury score = 0.88), leukotriene B4 (13.16 pg/mg tissue) and myeloperoxidase (115.6 pg/mg tissue) production compared to hemorrhaged C57Bl/6 mice (p<0.05). Conclusion: Complement activation is important in the development of hemorrhage-induced tissue injury and C5a generation is critical for tissue inflammation and damage. Thus, therapeutics targeting C5a may be useful therapeutics for hemorrhage-associated injury.
Keywords: Complement; Mucosa; Rodent